ANALISIS MANAJEMEN ARUS KAS TERKAIT KEBIJAKAN UANG KULIAH TUNGGAL DAN BIAYA KULIAH TUNGGAL SEKOLAH TINGGI AGAMA ISLAM NEGERI DI SULAWESI SELATAN - Fahri Abdullah (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This research was conducted with the aim to; analyzing cash flow management, reviewing the acceptance of the first one-year regular SPP S1 for STAIN students and the first year until the fourth year before and after the policy of Single Tuition and Single Tuition Fee (UKT-BKT) at the State Islamic High School in South Sulawesi. This research uses descriptive analysis and statistical test, statistic test on acceptance and use before and after UKT-BKT, done with t test for paired sample with SPSS (Statistical Package for the social science) with 90% confidence level (significant level ? = 0.05. With the aim of knowing whether there is a real difference in the acceptance of regular S1 SPP before and after the policy of UKT and BKT. The results of this study indicate that there is no significant mean difference between acceptance before and after UKT in the variables of use so as to be able to maintain the liquidity of cash flows at the two institutions. While the ratio analysis test shows the agency's ability to finalize short-term liabilities for current ratio, And for quick ratio shows the ability of both institutions to pay off current debt. In the Second Cash Ratio the agency can settle operational payments and programmed activities.Based on the analysis of cash ratio before and after UKT BKT in both institutions have Liquid cash means Both universities are able to pay off short-term debt and can run the program even though in 2015 until 2017 there is an outstanding debt but can be paid because the initial cash from KPPN as payment in advance.